Effect of cavitation on dispersion and emulsification process in high-pressure microsystems (HPMS). (22nd April 2016) - Gothsch, T.; Richter, C.; Beinert, S.; Schilcher, C.; Schilde, C.; Büttgenbach, S.; Kwade, A.
Abstract: The influence of cavitation on the dispersion and emulsification process in high pressure microsystems (HPMS) is still a controversially discussed issue. In this work cavitation in HPMS is investigated with laser induced fluorescence (LIF) and subsequently compared to dispersion and emulsification results at different backpressures in two different microchannel geometries. Additionally, velocity measurements with micro particle image velocimetry (µPIV) are presented. It is shown that cavitation influences the efficiency of the processes only in a negative way and that it does not contribute to the dispersion of particles or droplets. The positive effect of the attenuation and elimination of cavitation can be correlated to increased hydrodynamic stresses and increased turbulence, of which the latter especially affects the emulsification process. On basis of the results a new geometry was developed which features a significantly higher efficiency in the dispersion process. Highlights: Presence of cavitation deteriorates dispersion/emulsification process in high pressure microsystems. Suppression of cavitation to a certain extent increases dispersion and emulsification efficiency. Often applied T-geometry does not act, as widely expected, with an impact of the converging flows. A geometry which facilitates an impact of jets is presented which increases dispersion efficiency.